Տեղեկատվական պատերազմներ. Հնարքներն ու մեթոդները հակառակորդի քարոզչությունում - Աբրահամյան, Ն․
В данной статье автор, опираясь на конкретные инфо-политические факты со стороны Азербайджана, приводит важные информационные тезисы и выводы, употребляемые в агитации противника. На информационном поле битвы армянской стороны времена деятельности фидаинов давно прошли. Армянская сторона (Армения-Арцах-Диаспора) обязана работать систематизировано и последовательно. In this article the author, leaning on concrete info - the political facts from Azerbaijan, provides important information theses and the conclusions used in propaganda of the opponent. On an information field of fight of the Armenian party side times of fidains passed long ago. The Armenian side (Armenia-Artsakh-Diaspora) must work systematically and consistently.
Keywords: Ժուռնալիստիկա